Evaluation the effect of priming and its duration on germination characteristics of two lentil genotypes (Lens culinaris Medic.) under laboratory conditions - Seyyed jalal Azary; Mahdi Parsa; Ahmad Nezami; Reza Tavakol Afshari; Jafar Nabati (پژوهش‌های حبوبات ایران)
IntroductionLentil (Lens culinaris Medic.) as one of the oldest sources of human nutrition is of particular importance among beans due to the ease of digestion and high protein content. Priming method refers to a number of different seed characteristics improvements. In these methods, seeds are allowed to absorb some water so that the early stages of germination are performed, but the root can not grow. Due to the fact that lentil is usually cultivated in rain-fed areas and under dry conditions, it is often possible to provide sufficient moisture in the early stages of growth and germination for planting, in the early stage of growth and germination. Research results indicate that seed germination can be achieved through rapid germination, uniform appearance and strong establishment of the plant. One of the most important germination seed germination treatments is priming. Priming refers to a number of different seed improvement methods, in which all controlled seeding is applied. In priming, seeds are allowed to absorb some water so that the early stages of germination are performed, but the root can not be removed. In other words, the seeds go up to the second stage, but they do not enter the third stage. After priming treatments, the seeds are dried and cultivated as untreated seeds. Hydro priming is the simplest method for increasing the rate and percentage of germination and uniformity of deposition under stress conditions, especially in arid regions. In the experiment, which was performed on seed maize (Zea mays), it was observed that seed priming increased germination speed while the polyethylene glycol reduced the germination rate. In addition, hydro priming of seeds for 36 hours increased germination, root germination and seedling dry weight. The aim of this study was to investigate the effect of different priming treatments and the duration of priming on seed germination and growth seedling growth and selection of the most suitable treatment of two lentil genotypes. Materials & MethodsThis study was carried out in Ferdowsi University of Mashhad, Iran, as a factorial experiment based on completely randomized design with four replications in 2017. The treatments consisted of two lentil genotypes (Rabat and Kalposhch), six priming levels (non-priming (control), gibberellic acid (C19H22O6) 100 mg.l-1, Dayan seedlings solution 4 ml.l-1, potassium nitrate (KNO3) 500 mg.l-1, zinc sulfate (ZnSO4) 1000 mg.l-1 and hydro priming and priming duration (7 and 16 hours). After priming seeds were removed from the solutions and then placed in a laboratory for 24 hours until complete drying. Seeds were then disinfected 1% NaCl solution (NaClO) for five minutes and then washed three times with distilled water. Petri were also disinfected with 5% sodium hypochlorite solution. In the next step, 25 seeds were prepared from 12 cm diameter primer treatments between two layers of Watman filter paper and each petri was added to the required amount of distilled water. To germinate to a germinator by setting a temperature of ± 20° Celsius and the dark environment. The emergence of two-millimeter radicle length was considered as the beginning of seed germination and number of germinated seeds was daily recorded. At the end of 14th day, number of germinated seeds, seedling dry weight and length, root and shoot length and root and shoot dry weight were measured and germination indexes, such as germination percentage, germination rate and seed vigor were calculated.Results & DiscussionResults indicated that total number of germinated seeds, germination percentage and germination rate were significantly affected by genotype, priming component and interaction of genotype and priming duration. Robat genotype at 16 hours of priming had the highest number of germinated seeds, germination percentage and germination rate, but in Robat genotype with seven hours of priming, there was no significant difference observed. Root length was significantly affected by genotype and priming components. The best genotype for this characteristic was Robat and the most suitable priming treatment was control (non-priming). There were no statistically significant differences with zinc sulfate. The length of stems and seedling were affected by genotype, priming components and priming durations. For both characteristics, the best genotype, Rabat and the most suitable time, seven hours priming and for stem length, non-priming (control) was the best treatment, but there were no statistically significant differences with gibberellic acid, potassium nitrate and zinc sulfate. ConclusionResults of this study showed that Robat genotype has superior characteristics than Kalpush genotype, which can be used for cultivation. Generally, according to the results of this study, seed germination characteristics of these two lentil genotypes were positively affected priming treatments of gibberellic acid, potassium nitrate, zinc sulfate, Dayan solution and hydro priming. It seems that complementary studies on other compounds are needed to find suitable treatments for germination improvement